2010
DOI: 10.1159/000303528
|View full text |Cite
|
Sign up to set email alerts
|

Infections and Hardware Salvage after Deep Brain Stimulation Surgery: A Single-Center Study and Review of the Literature

Abstract: Aims: Infection of hardware is a serious complication after deep brain stimulation (DBS), as this may result in additional surgery, cost and loss of treatment benefit for the patient. We report the incidence and management of infections after DBS in a single institution over the past 11 years. Methods: A database of 270 patients with 484 implants was used in the study. Incidence, clinical characteristics and management of infections were analyzed. Results: The overall infection rate was 9.3% (25/270) by patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 36 publications
6
81
1
Order By: Relevance
“…The rate of infection, especially the 2.01%, compares favorably across published studies. Still, it is difficult to compare percentages directly because different authors use a variety of criteria to define postsurgical DBS infection [7,8,9,10,11,12,13,14,15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of infection, especially the 2.01%, compares favorably across published studies. Still, it is difficult to compare percentages directly because different authors use a variety of criteria to define postsurgical DBS infection [7,8,9,10,11,12,13,14,15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Various authors have stated that older age [25] and younger age [17] can increase the risk as well as that it is not a factor at all [9,10,12,13,26]. Bhatia et al [10] identified several other factors, asserting that skin erosion, medical comorbidities, scalp thickness and burr hole cap thickness were all either risks for infection or higher in the infected patients in their retrospective review. Sixel-Doring et al [26] in turn found that age, gender, disease duration, disease severity, hypertension and diabetes were not statistically more likely to cause infection in their PD population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25) Device infection is one of the most probable device-related complications in DBS. 2,4,10,14,17,22,24) Since the DBS procedure involves the implantation of a foreign body, the risk of infection is high. Recent reported incidence of device infection varies from 0.4% to 10%.…”
Section: Discussionmentioning
confidence: 99%
“…They are exceptionally rare intracranially (Sillay et al, 2008). In most cases of a bacterial infection at the DBS system mere antibiotic treatment does not eradicate bacteria completely so that the system or part of the system needs to be explanted and replaced after a period of consolidation (Bhatia et al, 2010). Apart from infections, skin erosions can be a problem (Sixel-Döring et al, 2010).…”
Section: Surgical Issues -Follow-up Of Wound Healing and Proper Technmentioning
confidence: 99%